Estimating Tax Incidence, Market Power and Market Conduct: The European Cigarette Industry - Sophia Delipalla; Owen O'Donnell (University of Kent, Department of Economics, 1999)
Recent theoretical work has shown that the incidence of ad valorem and specific taxes may differ and each may be over or under-shifted onto consumers in the presence of imperfect competition. These results are used to derive a method of estimating market power and conduct. An application is made to the European cigarette industry. Previous empirical comparison of the price effects of ad valorem and specific taxes is limited. For a group of countries with broadly similar cigarette industries, there is evidence of undershifting of both taxes, with the specific tax having a significantly greater impact on price. The extremes of both perfect competition and monopoly can be rejected. Behaviour is no less competitive than the equivalent of Cournot.
Keywords: H22; L13; L66; 330; Tax Incidence; Commodity Taxation; Market Power; Mark-up; Conjectural Variations; Cigarettes; Steuerinzidenz; Verbrauchsteuer; Marktmacht; Unvollkommener Wettbewerb; Tabaksteuer; Zigarettenindustrie; Theorie; EU-Staaten